Half-hazard : poems - Tracy, Kristen, 1972- (Graywolf Press, 2018)
"Half-Hazard is a book of near misses, would-be tragedies, and luck. As Kristen Tracy writes in the title poem, "Dangers here. Perils there. It'll go how it goes." The collection follows her wide curiosity, from growing up in a small Mormon farming community to her exodus into the forbidden world, where she finds snakes, car accidents, adulterers, meteors, and death-marked mice. These wry, observant narratives are accompanied by a ringing lyricism, and Tracy's knack for noticing what's so funny about trouble and her natural impulse to want to put all the broken things back together. Full of wrong turns, false loves, quashed beliefs, and a menagerie of animals, Half-Hazard introduces a vibrant new voice in American poetry, one of resilience, faith, and joy."--Amazon.com.